Historical identities : the professoriate in Canada - Stortz, Paul James, 1960-; Panayotidis, Euthalia Lisa, 1960- (University of Toronto Press, 2006)
As intellectual engines of the university, professors hold considerable authority and play an important role in society. By nature of their occupation, they are agents of intellectual culture in Canada. Historical Identities is a new collection of essays examining the history of the professoriate in Canada. Framing the volume with the question, 'What was it like to be a professor?' editors Paul Stortz and E. Lisa Panayotidis, along with an esteemed group of Canadian historians, strive to uncover and analyze variables and contexts - such as background, education, economics, politics, gender, and ethnicity - in the lives of academics throughout Canada's history. The contributors take an in-depth approach to topics such as academic freedom, professors and the state, faculty development, discipline construction and academic cultures, religion, biography, gender and faculty wives, images of professors, and background and childhood experiences. Including the best and most recent critical research in the field of the social history of higher education and professors, Historical Identities examines fundamental and challenging topics, issues, and arguments on the role and nature of intellectualism in Canada.